Critical appraisal of advance directives given by patients with fatal acute stroke: an observational cohort study. Issue 1 (December 2017) - Alonso, A.; Dörr, D.; Szabo, K.
Abstract Background Advance directives (AD) imply the promise of determining future medical treatment in case of decisional incapacity. However, clinical practice increasingly indicates that standardized ADs often fail to support patients' autonomy. To date, little data are available about the quality and impact of ADs on end-of-life decisions for incapacitated acute stroke patients. Methods We analyzed the ADs of patients with fatal stroke, focusing on: (a) their availability and type, (b) stated circumstances to which the AD should apply, and (c) stated wishes regarding specific treatment options. Results Between 2011 and 2014, 143 patients died during their hospitalization on our stroke unit. Forty-two of them (29.4%) had a completed and signed, written AD, as reported by their family, but only 35 ADs (24.5%) were available. The circumstances in which the AD should apply were stated by 21/35 (60%) as a "terminal condition that will cause death within a relatively short time" or an ongoing "dying process." A retrospective review found only 16 of 35 ADs (45.7%) described circumstances that, according to the medical file, could have been considered applicable by the treating physicians. A majority of patients objected to cardiopulmonary resuscitation (22/35, 62.9%), mechanical ventilation (19/35, 54.3%), and artificial nutrition (26/35, 74.3%), while almost all (33/35, 94.3%) directed that treatment for alleviation of pain or discomfort should be provided at all times even if it could hasten death. Conclusions The prevalence of ADs among patients who die from acute stroke is still low. A major flaw of the ADs in our cohort was their attempt to determine single medical procedures without focusing on a precise description of applicable scenarios. Therefore, less than half of the ADs were considered applicable for severe acute stroke. These findings stress the need to foster educational programs for the general public about advance care planning to facilitate the processing of timely, comprehensive, and individualized end-of-life decision-making.